2015
DOI: 10.5194/bg-12-6687-2015
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency and adaptability of the benthic methane filter at Quepos Slide cold seeps, offshore of Costa Rica

Abstract: Abstract. Large amounts of methane are delivered by fluids through the erosive forearc of the convergent margin offshore of Costa Rica and lead to the formation of cold seeps at the sediment surface. Besides mud extrusion, numerous cold seeps are created by landslides induced by seamount subduction or fluid migration along major faults. Most of the dissolved methane migrating through the sediments of cold seeps is oxidized within the benthic microbial methane filter by anaerobic oxidation of methane (AOM). Mea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 82 publications
0
2
0
Order By: Relevance
“…Petroleum droplets visibly seeped out of the sediment close to the core liner wall. High fluid flow through sediment cores can induce channelizing effects between the wall of the core liner and the sediment core, causing some fluid to move faster than the bulk volume (Steeb et al, 2014, 2015). Upon termination and slicing of the SOFT core we observed that although most of the petroleum seemed to be evenly distributed throughout the sediment, some petroleum accumulated in vein-like structures indicating such channelizing effects (Supplement 3).…”
Section: Resultsmentioning
confidence: 99%
“…Petroleum droplets visibly seeped out of the sediment close to the core liner wall. High fluid flow through sediment cores can induce channelizing effects between the wall of the core liner and the sediment core, causing some fluid to move faster than the bulk volume (Steeb et al, 2014, 2015). Upon termination and slicing of the SOFT core we observed that although most of the petroleum seemed to be evenly distributed throughout the sediment, some petroleum accumulated in vein-like structures indicating such channelizing effects (Supplement 3).…”
Section: Resultsmentioning
confidence: 99%
“…The AOM is always the predominant reaction in seep environments. In low-methane flux seep environments, all the methane can be consumed by AOM, while in high methane flux seep environments, a proportion of the methane may pass through the SMTZ and escape to the bottom water [25,26]. Both AOM and OSR processes strengthen the alkalinity of pore-water, which facilitates the precipitation of authigenic carbonate (Ca 2+ + HCO 3 − → CaCO 3 + H + ), and decrease the calcium concentration in pore-water.…”
Section: mentioning
confidence: 99%